Influence of cerclages on primary stability of tumor megaprostheses subjected to distal femur defects. Issue 2 (February 2016) - Jahnke, Alexander; Jakubowitz, Eike; Ishaque, Bernd Alexander; Rickert, Markus; Bischel, Oliver
Abstract: Backround: Purpose of this experimental study was to investigate the influence of cerclages on the primary stability of the MUTARS ® system using distally fractured synthetic femora. Methods: 4 MUTARS ® prostheses were implanted in synthetic femora respectively. Groups consisted of 4 intact bones, 4 fractured with cerclages and 4 fractured bones without cerclages. Spatial micromovements were measured with a high-precision rotational setup. Findings: The order from the weakest to the strongest torque transmission of the intact bones was rm1 -rm4 -rm2 -rm3 ( p = 0.011) and of the fractured bones with cerclages rm4 -rm1 -rm3 -rm2 ( p = 0.013). The MUTARS ® stems broke out of the fractured femoral shaft by removing cerclages ( p < 0.001) and by the influence of bone defect A ( p < 0.001). Overall micromovements of the intact bones were lower than those of the fractured bones without cerclages ( p < 0.001) and overall micromovements of the fractured bones with cerclages were lower than those of bones without cerclages ( p < 0.001). Interpretation: Due to high press-fit at the proximal and distal isthmus region fissural fractures of the femur may occur. This should always be taken into account. It is advisable to secure them and provide a prophylaxis for these fissural fractures by means of cerclages.